Restructuring Restaurant Work: Employer Responses to Local Labor Standards in the Full-Service Restaurant Industry. Issue 2 (March 2020) - Lester, T. William
Recent research shows that increasing the minimum wage does not result in significant job losses. Yet, there is still uncertainty as to how higher labor standards may reshape employment practices within firms. This article directly examines employer responses to higher labor standards through a qualitative case comparison of the full-service restaurant industry across two fundamentally different institutional settings: San Francisco—with the nation's highest minimum wage and related mandates—and North Carolina's Research Triangle region. Evidence shows that higher labor standards led to wage compression even while some employers offered higher benefits to reduce turnover. San Francisco employers seek higher-skilled, more professional workers, rather than invest in formal in-house training, and find better matches. Yet, higher-wage mandates have exacerbated the wage gap between occupations, and some employers have responded by radically restructuring industry compensation practices by adding service charges and eliminating tipping.